Characterization of the complete mitochondrial genome of a nematode species, Caenorhabditis tribulationis (Nematoda, Rhabditidae) - Yuheng Liu; Zhang Jingjing; Chao Li (Mitochondrial DNA. Part B. Resources, 2022)
In the present study, we reported the complete mitogenome sequence of Caenorhabditis tribulationis Stevens & Félix 2019. The whole mitogenome of C. tribulationis is 14006 bp in length with an extreme bias of high AT content (75.26%) (GenBank accession no. OL362111). The mitochondrial genome contains 12 protein-coding genes (PCGs), 22 transfer RNA (tRNAs) genes, 2 ribosomal RNA (12S rRNA and 16S rRNA) genes, and a control region. All genes were unidirectionally transcribed on the same strand, typical for other nematode mitogenomes. 9 PCGs were initiated by typical ATN codons, except for NAD2, CYTB and NAD4, which were start with TTG codons. All the PCGs were predicted to use the typical TAN as the stop codons. The phylogenetic analysis showed that the relationship of C. tribulationis is very close to other species in the family Rhabditidae and separated form species of the families Ascarididae, Toxocaridae, Anisakidae and Ascaridiidae with high bootstrap value support.